Polymer-based nanoparticles in targeted cancer therapy: a review - Farah Al-Sahlawi,, Aya Yaseen Mahmood Alabdali, Sasikala Chinnappan, Ali Al-Samydai, Marwan Abdelmahmoud Abdelkarim Maki (Journal of Applied Pharmaceutical Science, 2024)
Tumors are the result of unchecked cell proliferation in the body, which leads to the complicated and widespread illness known as cancer. The formidable issue of providing effective cancer treatment has prompted scientists to investigate novel strategies. Using nanoparticles based on polymers tiny particles made of substances that are harmless for the body is one approach that shows promise. Strong anticancer medications are delivered to cancer cells directly via these nanoparticles, which also increase therapy effectiveness and reduce adverse effects on healthy cells. This study explores the field of targeted cancer treatment using polymer-based nanoparticles, using information from reliable sources such as PubMed, Web of Science, and Scopus. A strict and methodical procedure was followed in the selection of published articles to guarantee the inclusion of relevant and excellent research papers. Numerous production techniques, including self-assembly, emulsion/solvent evaporation, and nanoprecipitation, provide fine control over the size, shape, and properties of nanoparticles. Methods based on ligands, pH response, and stimuli response are used to promote enhanced selectivity and accumulation inside malignancies. Diverse advantages are provided by polymer-based nanoparticles for targeted cancer therapy. Their promise in targeted cancer therapy is highlighted by this comprehensive review, which also provides insights into design concepts, manufacturing techniques, and targeting strategies that open the door to individualized and successful therapies. The benefits of polymer-based nanoparticles are emphasized, including their strong drug-loading ability, prolonged half-life, and active targeting of cancer cells with the least amount of damage to healthy tissues. In order to maximize the usage of polymer-based nanoparticles in customized cancer therapies and eventually improve patient outcomes in the area of oncology, further investigation and clinical trials are necessary.
Keywords: Cancer, polymer-based nanoparticles, anticancer drugs, targeted therapy, tumor targeting, drug delivery, nanoparticle applications, manufacturing methods, self-assembly, emulsion/solvent evaporation